Controlling the Emission Properties of Quantum Rods via Multiscale 3D Ordered Organization. (24th November 2021) - Bizien, Thomas; Postic, Marie; Even-Hernandez, Pascale; Panizza, Pascal; Mériadec, Cristelle; Meneau, Florian; Mazari-Arrighi, Elsa; Dupuis, Christophe; Gosse, Charlie; Cotlet, Mircea; Gang, Oleg; Marchi, Valérie; et al.
Abstract : A specific organization of optically active nanoscale objects can greatly affect the optical response of a system. Here, we report the controlled modification of the fluorescent emission by the assembly of water-soluble quantum rods (QRs). Our study combines optical, electron microcopy, and X-ray scattering characterizations to reveal a correlation between the self-assembly behavior of QRs into ordered 3D-arrays and the optical properties (luminescence) of formed assemblies, where the observed optical response is highly dependent on the QR aspect ratio. Specifically, shorter, 18 nm long QRs (QR18 ), exhibiting a well-defined smectic packing, demonstrate an enhancement of the emission intensity accompanied by a red shift and a lifetime reduction. In contrast, 40 nm long QRs (QR40 ), forming a columnar phase, does not show these optical properties.